Investigation on Bursa Fabricius and Body Weights in Broiler and Local Chicks Vaccinated with Two Types of Infectious Bursal Disease Vaccines - Al-Mayah, Ali A.S.; Tabeekh, Mudhar A.S. Abu (International Journal of Poultry Science, 2010)
Forty five Hubbard broiler chicks and Forty five local chicks of one day old were reared on litter floor for 35 days. The chicks were divided into six groups A, B and C for broiler chicks, D, E and F for local chicks. The chicks of group A and D were vaccinated with an intermediate vaccine (Bursine®-2) whereas, the chicks of group B and E were vaccinated with an intermediate-plus type of vaccine (Bursine® Plus). Vaccination has been performed at 14th day. The chicks of group C and F were acted as control. Five chicks were sacrificed by decapitation from the experimental groups at 21st, 28th and 35th day and the bursae were removed, bursa weight (gram) and body weight (gram) were recorded for each individual bird. Significant decrease of bursa weight (p<0.05) was found in group B compared with that of group C at 21st day. The bursa weights in group D and E of local chicks were significantly differed at (p<0.05) from that of control group (F). The body weights of group D and E of local chicks were significantly decreased from those of group F at (p<0.05). The present study revealed that the more pathogenic intermediate vaccine (intermediate-plus) caused severe bursa of Fabricius injury in vaccinated local chicks. This could be explained by the lower degree of attenuation of this kind of vaccine and may be also related to the lack of maternally-derived antibody in these chicks.